2010
DOI: 10.1063/1.3457151
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreflectance of metal transducers for time-domain thermoreflectance

Abstract: We report measurements of the temperature dependence of the optical reflectivity, i.e., the thermoreflectance dR / dT, of 18 metallic elements at two laser wavelengths commonly used in ultrafast pump-probe experiments, 1.55 m and 785 nm. The thermoreflectance is determined using time-domain thermoreflectance combined with measurements of the laser power and spot size and comparisons between the data and quantitative modeling of the temperature evolution at the surface of the sample. At a laser wavelength of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 31 publications
11
66
0
Order By: Relevance
“…In the cases of PtSi, NiSi, CoSi 2 , TiSi 2 (C54), we found that the temperature dependence of reflectivity at 300K is comparable to the best previously reported materials 42 at λ=785 nm. The thermoreflectance coefficients of CoSi 2 films had a positive value, while TiSi 2 , NiSi and PtSi exhibited negative values.…”
Section: B Transport Characterizationsupporting
confidence: 63%
“…In the cases of PtSi, NiSi, CoSi 2 , TiSi 2 (C54), we found that the temperature dependence of reflectivity at 300K is comparable to the best previously reported materials 42 at λ=785 nm. The thermoreflectance coefficients of CoSi 2 films had a positive value, while TiSi 2 , NiSi and PtSi exhibited negative values.…”
Section: B Transport Characterizationsupporting
confidence: 63%
“…5. The TDTR apparatus we use to measure dR dT at 0.785 µm has been described previously [12,19] and is nearly identical to that described above, but uses a Ti:sapphire laser with a fundamental wavelength of 0.785 µm. As expected, Au, Al, and Ta show large values of the thermoreflectance at wavelengths nearby in energy to band resonances at ≈0.5, 0.6, and 0.8 µm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous qualitative measurements of the thermoreflectance coefficient, dR dT , of metallic elements [8][9][10][11], however only a few studies report quantitative values at isolated optical wavelengths [12][13][14][15]. Furthermore, it is prohibitively difficult to predict the thermoreflectance of a metal from other material properties because the temperature dependence of the optical constants [9] of metals depend on several factors: changes in the electron bands created by thermal expansion, changes in occupations of electron states near the Fermi level, and changes in the phonon population that alter electron scattering rates and perturb the electron energy bands through electron-phonon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The pump beam is modulated at a frequency of $10 MHz, and this beam passes through the transparent fused silica substrate and heats the aluminum surface of the sample. The reflectivity of aluminum 23 exhibits a relatively large change with respect to temperature near 800 nm, and this thermally induced change in reflectivity is monitored with the timedelayed probe beam. The arrival time of the probe beam at the surface of the sample is adjusted with the use of a mechanical delay stage, and the reflected intensity of the probe The uncertainty values for G represent the range of values that could fit our experimental data given the propagation of uncertainties in our experimental data and in the parameters that are input to our thermal model (e.g., metal film thicknesses and conductivities).…”
mentioning
confidence: 99%